Valuation and perception of the costs of climate change on health - Nordeng, Zuzana; Kriit, Hedi; Poltimäe, Helen; Aunan, Kristin; Dahl, Miriam S.; Jevtic, Marija; Matkovic, Vlatka; Sandanger, Gunnell; Orru, Hans (Scandinavian journal of public health, 2024)
Background and aims: Climate change affects our societies and lives through our economies, our livelihoods, and our health. Economic losses of climate change are estimated at $23 trillion, largely through externalities due to premature mortality, healthcare expenditure, and health-related work losses. Even if there are established methods to quantify the health economic burden, there is limited information on how people perceive this information. The current study aimed to examine different health cost evaluation methods and observe perceptions of stakeholders in the climate change context. - Method: The participatory research approach of the World Café with 41 participants was applied to explore four topics associated with valuing the costs of climate change. The data were analyzed following an inductive approach. - Results: Despite the willingness-to-pay approach being widely applied, many experts see actual healthcare costs as a more explicit indicator of costs; however, this approach might underestimate actual costs. Participants experienced difficulties accepting and understanding cost estimates that indicated very high externalities as a percentage of gross domestic product. The cost-effectiveness of mitigation and adaptation measures was also challenged by a concern that while the costs of such measures are incurred now, the benefits do not come to fruition until later, for example, when building bike lanes or dams. - Conclusions: Policies should favor environmentally friendly activities such as making cycling more convenient in cities with the health benefits presented in monetary terms, while limiting car driving. Moreover, the public might better understand the costs of climate change via tools that map how solutions influence different sectors and outlining the costs in evaluating the benefits for health and the environment.
Zuerst online veröffentlicht: 14. Juni 2024
Gesehen am 27.11.2024